Relationship Between Baroreflex and Cerebral Autoregulation in Patients With Cerebral Vasospasm After Aneurysmal Subarachnoid Hemorrhage - Uryga, Agnieszka; Nasr, Nathalie; Kasprowicz, Magdalena; Budohoski, Karol; Sykora, Marek; Smielewski, Peter; Burzyńska, Małgorzata; Czosnyka, Marek (Frontiers in Neurology, 2022)
Introduction The common complications following aSAH are cerebral vasospasm (CV), impaired cerebral autoregulation (CA), and disturbances in the autonomic nervous system, as indicated by impaired baroreflex sensitivity (BRS). The compensatory interaction between BRS and CA has been shown in healthy volunteers and stable pathological conditions such as carotid atherosclerosis. The aim of this study was to investigate whether the inverse correlation between BRS and CA would be lost in patients after aSAH during vasospasm. A secondary objective was to analyse the time-trend of BRS after aSAH. Materials and Methods Retrospective analysis of prospectively collected data was performed at the Neuro-Critical Care Unit of Addenbrooke’s Hospital (Cambridge, UK) between June 2010 and January 2012. The cerebral blood flow velocity (CBFV) was measured in the middle cerebral artery using transcranial Doppler ultrasonography (TCD). The arterial blood pressure (ABP) was monitored invasively through an arterial line. Cerebral autoregulation was quantified by the correlation coefficient (Mxa) between slow oscillations in ABP and CBFV. BRS was calculated using the sequential cross-correlation method using the ABP signal. Results 73 aSAH patients were included. The age [median (lower-upper quartile)] was 58 (50-67). WFNS scale was 2 (1-4) and Modified Fisher scale was 3 (1-3). In the total group, 31 patients (42%) had CV and 42 (58%) had no CV. ABP and CBFV were higher in CV patients during vasospasm compared to non-CV patients (p = 0.001 and p < 0.001). There was no significant correlation between Mxa and BRS in patients with CV, neither during nor before vasospasm. In patients without CV, a significant, although moderate correlation was found between BRS and Mxa (rS = 0.31; p = 0.040), with a higher BRS associated with worse CA. Multiple linear regression analysis showed a significant relationship between BRS and days elapsed after aSAH in patients with CV (Rp = -0.42; p < 0.001). Conclusions Inverse compensatory correlation between BRS and CA was lost in patients who have developed CV after aSAH, both before and during vasospasm. The way these findings contribute to the prognosis of these patients should be investigated in larger studies.